Effect of Mg, B, Zn and Mo on lettuce production - Fontes, Ruy Rezende; Lima, José de Almeida; Torres, Antonio Carlos; Carrijo, Osmar Alves (Pesquisa Agropecuaria Brasileira, 2014)
To evaluate the effects of soil applications of magnesium sulfate (200 kg/ha), borax (20 kg/ha), zinc sulfate (20 kg/ha) and sodium molybdate (2 kg/ha)on the lettuce(Lactuca sativa L.) cultivars 'Loura do Pleuré, 'Aurélia' and 'Brasil-48', two experiments were carried out during the rainy season of 1977 and 1978, on a Dark-Red Latosol underformer 'Cerrado' (savannah) vegetation all the CNPHorlaliças, in both experiments there was a significant effect of zinc for all the evaluated parameters and the 1978 trial also uncovered the importance of molybdenum on lettuce production. The cultivars 'Loura do Pleuré' and 'Aurélia' were the most productive ones, and did notl differ significantly from each other; however they did differ from 'Brasil-48'. There was no significant effect of the interaction cultivars x fertilizer levels.